A liénard oscillator resonant tunnelling diode-laser diode hybrid integrated circuit: model and experiment - Slight, Thomas James (2012)
We report on a hybrid optoelectronic integrated circuit based on a resonant tunnelling diode driving an optical communications laser diode. This circuit can act as a voltage controlled oscillator with optical and electrical outputs. We show that the oscillator operation can be described by Liénard’s equation, a second order nonlinear differential equation, which is a generalization of the Van der Pol equation. This treatment gives considerable insight into the potential of a monolithic version of the circuit for optical communication functions including clock recovery and chaotic source applications.